Biomimicry improvement of school shuttle routing: incorporating demand balancing nodes - A. Ozor, P.; Mbohwa, C. (International Journal of Engineering and Technology, 2018)
Campus communities in some developing countries are predisposed to multiple modes of transport services (vehicle, motorcycle, tricycle). The security concerns in such area may lead to prohibition of one or more of the existing systems with a consequent unbearable hardship to the community. This study investigated the use of Bio-mimicking based algorithm- Ant Colony Optimization and incorporation of demand balancing nodes to determine an effective shuttle routing plan in a Campus community. The approach was applied to a specific example Campus, namely; Shuttle routing problem in a Nigeria public University. From the analysis of all the data collected for the study, five and three additional shuttle terminals were created for the hypothetical Northern and Southern zones respectively. The distances travelled by the shuttles in the new routes varied from a minimum of 1537.64m to a maximum of 3912.27m in the Northern zone. The mean route distance in the zone is 2509.25m. Similarly, the Southern zone routes have distances varying from 1932.43m to 2260.8m, with a mean route distance of 2120.42m. Comparatively, the shuttle route distances in the existing routes varied from 4134.55m 4706.08m with a mean route distance of 4481.99m. The results show that an average distance reduction of 44% was observed for shuttle routes in the Northern zone. The results also show that average distance reduction of over 52% is obtainable for shuttle routes in southern zone.